OPTIMIZATION OF HADRAH EXTRACURRICULAR ACTIVITIES IN IMPROVING SCHOOL COMPETITIVENESS AT SMP NEGERI 4 PURWOREJO - Ayu Novitasari; Ida Faridah; Mohamad Madum (Al-Mubin, 2026)
Educational Management has an important role in increasing school competitiveness, one of its activities in the non-academic field is through Hadrah extracurricular activities carried out in public schools. This study aims to analyze the optimization of Hadrah extracurricular activities in increasing school competitiveness at SMP Negeri 4 Purworejo . This study uses a descriptive qualitative research method. The research location is at SMP Negeri 4 Purworejo. Data were obtained through observation, documentation and interviews with the Head of Student Affairs, Head of Hadrah Extracurricular Activities, and Hadrah extracurricular participants. Data analysis techniques use reduction, display and verification. Data validity techniques use triangulation. The results of this study indicate that the optimization of Hadrah extracurricular activities in increasing school competitiveness at SMP Negeri 4 Purworejo includes: 1) Planning such as compiling Hadrah program objectives and compiling Hadrah program plans; 2) Organizing such as forming a person in charge of Hadrah activities and recruiting Hadrah program participants; 3) Implementation includes the implementation of Hadrah program development, the availability of infrastructure, the availability of funding sources; 4) Evaluation includes practical exam activities and monitoring and evaluation of hadrah activities every 3 months